Permasalahan Literasi Dalam Perilaku Mencontek Di SDN 02 Neglasari - Renata Nur Annisa; Dinie Anggraeni Dewi; Rizky Saeful Hayat (Pendekar : Jurnal Pendidikan Berkarakter, 2024)
Basically, education is one of the most important factors in improving human resources and the nation's standard of living. In the midst of rapid world change, students need cultural and civic literacy so they can maintain their identity as Indonesians and can live together in diversity both within the school environment and in the community. Cheating is something that is often encountered in the learning process. Cheating is one of the efforts made by students to get good grades in an easy and short way.